Design, synthesis, and antifungal activities of novel triazole derivatives containing the benzyl group - Xu K; Huang L; Xu Z; Wang Y; Bai G; Wu Q; Wang X; Yu S; Jiang Y (Dove Medical Press, 2015)
Kehan Xu,1,* Lei Huang,1,* Zheng Xu,2 Yanwei Wang,1,3 Guojing Bai,1 Qiuye Wu,1 Xiaoyan Wang,1 Shichong Yu,1 Yuanying Jiang1 1School of Pharmacy, Second Military Medical University, Shanghai, 2Shanghai Changzheng Hospital, Second Military Medical University, Shanghai, 3Number 422 Hospital of PLA, Zhanjiang, People’s Republic of China *These authors contributed equally to this work Abstract: In previous studies undertaken by our group, a series of 1-(1H-1,2,4-triazole-1-yl)-2-(2,4-difluorophenyl)-3-substituted-2-propanols (1a–r), which were analogs of fluconazole, was designed and synthesized by click chemistry. In the study reported here, the in vitro antifungal activities of all the target compounds were evaluated against eight human pathogenic fungi. Compounds 1a, 1q, and 1r showed the more antifungal activity than the others. Keywords: triazole, synthesis, antifungal activity, CYP51